2017
DOI: 10.1111/tme.12429
|View full text |Cite
|
Sign up to set email alerts
|

Blood donors' attitudes towards voluntary non‐remunerated donation in Trinidad and Tobago

Abstract: Despite low awareness of blood shortage, willingness to become VNRD was high among existing donors. Accountability and donor convenience underpinned the main motivators for converting to VNRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It has revealed a deficiency in public information about voluntary non‐remunerated donation . Similarly, existing F/R and voluntary donors need more information before converting to VNRD . Lack of information about blood donor selection criteria contributes to a high donor deferral rate .…”
Section: Introductionmentioning
confidence: 99%
“…It has revealed a deficiency in public information about voluntary non‐remunerated donation . Similarly, existing F/R and voluntary donors need more information before converting to VNRD . Lack of information about blood donor selection criteria contributes to a high donor deferral rate .…”
Section: Introductionmentioning
confidence: 99%
“…High knowledge, positive attitudes and willingness to donate VNR blood have been demonstrated among all sociodemographic groups in two community KAP studies from TTO 6,26 . A study of existing FRDs in that country also revealed willingness to convert to VNRDs 30 . The message from these studies was that filling specific knowledge gaps, improving communication and enhancing donation arrangements could convert this willingness to actual voluntary nonremunerated donation 6,26,27 .…”
Section: Discussionmentioning
confidence: 95%
“…A recent study from Trinidad and Tobago (TRT) examined approximately 1000 adults presenting for blood donation and administered a questionnaire intended to determine the willingness of FRD (98% of TRT) to become VNRD (Charles et al, ). The population comprised 24% 17–26‐year‐olds and 35% 27–36‐year‐olds, and 34% were female.…”
Section: Resultsmentioning
confidence: 99%